Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Hey i am only wondering if it is possible that the equation below holds:

$$ \sum\limits_{i=0}^{\infty} a_i(b_i - c_i) = \sum\limits_{i=0}^{\infty} (a_ib_i - a_ic_i) =\sum\limits_{i=0}^{\infty} a_ib_i - \sum\limits_{i=0}^{\infty} a_ic_i $$


share|cite|improve this question
You appear to have a typo: I think that you mean $$\sum_{i=0}^\infty a_i(b_i-c_i)=\sum_{i=0}^\infty(a_ib_i-a_ic_i)=\sum_{i=0}^\infty a_ib_i-\sum_{i=0}^\infty a_ic_i\;.$$ Yes, provided that the three series all converge. – Brian M. Scott Mar 18 '13 at 20:29
It was a typo yes. I fixed it. – 71GA Mar 18 '13 at 20:36
No, you haven't. $a(b-c)=ab-ac$ and not $ab-bc$. – Asaf Karagila Mar 18 '13 at 20:37
Should still be $a_ic_i$ not $b_ic_i$. – Thomas Andrews Mar 18 '13 at 20:37
I did fix that thanks! – 71GA Mar 19 '13 at 6:16
up vote 2 down vote accepted

Recall the definition of a series is: $$\sum_{i=1}^\infty a_i=\lim_{n\to\infty}(a_1+\ldots+a_n).$$

The answer to your question follows from the fact that: $$\lim_{n\to\infty}a_n(b_n-c_n)=\lim_{n\to\infty}a_n b_n-\lim_{n\to\infty}a_n c_n,$$ whenever all the limits have a finite value.

share|cite|improve this answer
@GitGud: Finite in the sense that the actual limit of the series is finite. Not the index set. – Asaf Karagila Mar 18 '13 at 20:31
A small misunderstanding on my part. Sorry. – Git Gud Mar 18 '13 at 20:32
@GitGud: You should have left the comment, it was a good remark that made the answer slightly better understood. But I suppose a small edit would be even better. – Asaf Karagila Mar 18 '13 at 20:36

It holds when $$\sum_{i=0}^\infty a_i b_i$$ and $$\sum_{i=0}^\infty b_i c_i $$ ar both unconditional convergent.

Or $$ \sum_{i=0}^\infty a_i (b_i - c_i)$$ is unconditional convergent.

This is in the finite dimensional the case when they are absolute convergent, that means when $$\sum_{i=0}^\infty |a_i b_i|$$ is convergent.

share|cite|improve this answer
Do you really need absolute convergence? – Asaf Karagila Mar 18 '13 at 20:28
Do you have an example for when this fails for a conditionally convergent series? – Asaf Karagila Mar 18 '13 at 20:30
Interesting. I thought that $0=0$. – Asaf Karagila Mar 18 '13 at 20:33
but $\infty -\infty$ is not zero, it is indeterminate – Dominic Michaelis Mar 18 '13 at 20:33
But then $\sum a_ib_i=\infty$. This is not about conditional convergence anymore. It's just not a convergent series. – Asaf Karagila Mar 18 '13 at 20:35

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.